A new Mexican species of Paraxenylla (Collembola: Hypogastruridae) from marine littoral sand of Quintana Roo, Mexico - José G. Palacios-Vargas; Magdalena Vázquez (Revista Mexicana de Biodiversidad)
The new species Paraxenylla mahahualana sp. nov. from Quintana Roo is described, it is similar to P. cubana, and shares the presence of ventral tube with 1 + 1 seta but differs in having tibiotarsi with 5 tenent hairs and 5 cylindrical sensilla on antennal segment IV and 3 + 3 tenacular teeth. A key for the 10 species known in the genus is also given.